Determinants for Spatial Location of Pharmacies; Determinanty lokalizacji przestrzennej aptek - Maciej Jewczak (Comparative Economic Research. Central and Eastern Europe, 2012)
The topic of drug reimbursement is an important subject when one makes a decision on the construction of the reform of the health sector. Any change in the reimbursement list ends with a hot debate in the media and in everyday life. Incomprehensible pricing strategies used by pharmacies, force patients to seek those places that offer the necessary medication at the lowest possible price. Recognizing the economic opportunities for a profitable business, in recent years, a significant increase in the number of pharmacies is observed, and therefore, the number of these entities makes the process of selling drugs, especially those from the reimbursement list, almost impossible to control. The article aims to reveal the spatial dependence for the pharmaceutical market on the example of pharmacies in poviat districts of Poland. An attempt is made to assess the prevalence of spatial dependence between the number of pharmacies and other determinants indicating health care resources, ageing process and the state of health of Poles. The summary of the study is to build a spatial model with its diagnosis for the number of pharmacies according to various socio-economic factors. – – Tematyka refundacji lekoẃ to istotne zagadnienie przy podejmowaniu wszelkich decyzji dotyczacych kształtu reform dla sektora opieki zdrowotnej. Kazḋorazowa zmiana wykazu lekoẃ refundowanych konćzy sie goraca debata w mediach i w codziennym zẏciu. Niezrozumiałe strategie cenowe, stosowane przez apteki, zmuszaja pacjentoẃ do poszukiwania tych miejsc, ktoŕe oferuja niezbedny lek w jak najnizṡzej cenie. Dostrzegajac mozl̇iwosći dobrego biznesu ekonomicznego, na przestrzeni ostatnich lat, obserwuje sie znaczacy wzrost liczby aptek, a w zwiazku z tym, liczebnosćt́ych podmiotoẃ uniemozl̇iwia pełna kontrole w procesach sprzedazẏ lekoẃ, zwłaszcza tych z list refundowanych. Celem artykułu jest wykazanie przestrzennych zalezṅosći obserwowanych na rynku farmaceutycznym na przykładzie liczby aptek w powiatach Polski. Podjeta została prob́a oceny wystepowania przestrzennych zalezṅosći pomiedzy liczebnosćia aptek a liczba lekarzy, liczba zakładoẃ opieki zdrowotnej, jak roẃniezi̇nnych determinant wskazujacych na proces starzenia sie społeczenśtwa i stanu zdrowia Polakoẃ. Podsumowaniem badanj́est prob́a budowy modelu przestrzennego i jego diagnoza dla liczby aptek w zalezṅosći od roźṅych czynnikoẃ społeczno-gospodarczych.
Keywords: 330